ANALISIS USAHA PEMANFAATAN KULIT BUAH KAKAO (Theobrama Cacao L.) FERMENTASI DENGAN CAIRAN RUMEN TERHADAP SAPI PERANAKAN ONGOLE (PO) - Surya Winarto (Universitas Sumatera Utara, 2012)
Abstrac: The research was conducted in Biology Laboratory of agricultural faculty university of north sumatera, Medan from October 2011 until January 2012. Investigate economic anaysis of fermented caco pod (Theobrama cacao L.) by rumen fluid on ongole crossbred cattle pattening. Methodology which was used Latin Square design with 4 treatments. Treatments are P0 (0% of fermented pod cacao), P1 (10% of fermented pod cacao), P2 (20% of fermented pod cacao), P3 (30% of fermented pod cacao). The results showed that on average profit / loss the was at highest at P0 of Rp. 527 405,- and the lowest was on P3 of Rp. 426 786,-. Average benefit cost ratio (B/C) was highest at P0 of 1.10, and 1.07 for the smallest at P3. Average Break Event Point (BEP) BEP which consist of the highest production rates was on P3 of Rp. 23 375,- as the highest and the lowest at P0 of Rp. 23 016,-. Average BEP highest production volume was of 239 kg on P2 and P0 for the smallest at 234 kg. Average income over feed cost (IOFC) was highest at P0 Rp. 597 718, P3and lowest at Rp. 476 339, -. Average return on investment (ROI) the highest of 11.80% at P0, and the smallest at 7.94% in P3. As conclusion wast that the use of fermented cacao pod with rumen fluid in cows given Ongole crossbred male fattening give benefits and could be used for the cattle business. Keywords: Economic Analysis, cacao pod, Fermentation, Rumen Fluid, Ongole crossbred cattle